Grupo de pais: um dispositivo potencializador da escolarização de alunos com autismo - Almeida, Daniela Durigon (2022)
The main goal of this research project is to identify parents’ top demands regarding development and schooling of their children with autism. The theme is justified for being an institutional request from the researcher’s previous professional context, where it was necessary to get to know the demands from parents of children with structural barriers on their psychic formation, and, from this, create a host space for these families. This set of strategies is based on the premise that parents’ actions before their children directly influence both kids’ schooling and formation. It is a qualitative research, that used a questionnaire, and therapeutic and pedagogical reports for data production. The participants of this research were five parents of children with autism that are attended in two service centers. Authors such as Kupfer et al. (2017), Laznik (2013), Jerusalinksy (2012) provide theoretical basis for this research. Data was analyzed according to the four foundations of Psychoanalytical Evaluation at the age of 3, together with a category that aimed to examine the demands in the parents’ answers. As a result, guidelines for the implementing of parents’ groups were made, seeking to potentialize the schooling of children with autism. At the end of this research, it was concluded that parents present demands associated with themes such as development, rights, inclusion, and schooling.